STRATEGIES OF FEMALE RESISTANCE IN IBRAHIM NASRALLAH’S A'ROS AMINAH: A POSTCOLONIAL FEMINIST ANALYSIS - Miftahul Ilmia; Misbahus Surur; Arif Mustofa (Arabic Literature Department, 2024)
This study analyses the strategies employed by female characters, particularly Aminah in Ibrahim Nasrallah's novel A'ros Aminah, to resist and challenge the oppressive characteristics of Israeli colonialism. The resistance is demonstrated by female characters in the novel from the perspective of postcolonial feminist studies. Postcolonial feminism is a multidisciplinary area of study that examines the convergence of feminist and postcolonial philosophies. The analysis centers on examining the profound impact of colonialism on the marginalization of women's dignity. This study utilizes a descriptive qualitative research methodology to analyze the behaviors and resistance of Aminah and other female characters in novel narratives. The study's data include quotations that portray the acts of resistance demonstrated by women throughout the conflict between Palestinian and Israeli soldiers. The quotes in the collection are analyzed using postcolonial feminist theory to investigate how women in the novel engage in resistance. The study findings suggest that the female characters in the novel are depicted as independent women who actively work towards their survival, possess the capability to support their families, and exhibit a distinct ability to oppose the Israeli army. The research findings indicate that women can actively resist and counteract the oppression that occurred during the conflict between the Palestinians and Israel.